Implication of Gypsum Rates to Optimize Hydraulic Conductivity for Variable‐Texture Saline–Sodic Soils Reclamation. (14th August 2015) - Ahmad, Sagheer; Ghafoor, Abdul; Akhtar, Muhammad E.; Khan, Muhammad Z.
Abstract: Sodium (Na + ) dominated soils reduce saturated hydraulic conductivity ( Ks ) by clay dispersion and plugging pores, while gypsum (CaSO4 2H2 O) application counters these properties. However, variable retrieval of texturally different saline–sodic soils with gypsum at soil gypsum requirement (SGR) devised to define its quantity best suited to improve Ks, leach Na + and salts. This study comprised loamy‐sand (LS), sandy loam (SL), and clay loam (CL) soils with electrical conductivity of saturation extract (ECe ) of ~8 dS m −1, sodium adsorption ratio (SAR) of ~44 (mmol L −1 ) 1/2 and exchangeable sodium of ~41%, receiving no gypsum (G0 ), gypsum at 25% (G25 ), 50% (G50 ) and 75% (G75 ) of SGR. Soils packed in lysimeters were leached with low‐carbonate water [EC at 0·39 dS m −1, SAR at 0·56 (mmol L −1 ) 1/2 and residual sodium carbonate at 0·15 mmolc  L −1 ]. It proved that a rise in gypsum rate amplified Ks of LS ≫ SL > CL. However, Ks of LS soil at G25 and others at G75 remained efficient for salts and Na + removal. Retention of calcium with magnesium (Ca 2+  + Mg 2+ ) by LS and SL soils increased by G50 and decreased in G75, while in CL, it also increased with G75 . The enhanced Na + leaching efficiency in LS soil with G25 was envisaged by water stay for sufficient time to dissolve gypsum and exchange and leach out Na + . Overall, the superiority of gypsum for LS at G25, SL at G50 and CL at G75 predicted cost‐effective soil reclamation with a decrease in ECe and SAR below 0·97 dS m −1 and 5·92 (mmol L −1 ) 1/2, respectively. Copyright © 2015 John Wiley & Sons, Ltd.